Effective Material Management for Building Construction Industry: Addressing the Challenges of Material Management in the Construction Industry (Journal of Advances and Scholarly Researches in Allied Education, 2018)
India is rapidly developing the country and construction industry is lagging behind in use of information technology as compared to other major industries in the country. Results suggest that materials which are being used for construction costs around 50-60 of total project cost, Advance systems which are existing today are have some limitations to manage it’s flow and control it’s wastage. Even today material management at construction sites are carried out by some traditional methods and heavily depends on human skills. The Main hurdle of material management in use of ICT is shortage of user-friendly software.